Prescribing English, producing silence: How English classes in the medical vocational school systemically undermine communicative competence - Hendra Nugraha; Diba Yuri Mustafa; Leil Badrah Zaki (Journal of Research on English and Language Learning (J-REaLL), 2026)
While English for medical purposes (EMP) is indispensable for the advancement of global healthcare, empirical investigations into its application within Indonesian medical vocational schools (MVS), which serve as a pivotal contributor to the national labor force, remain limited. In order to address this gap, the present study explores EMP within a strategically selected MVS in the Riau Islands through a mixed-methods research design. Data were collected through semi-structured interviews with both administrative personnel (n=2) and educators (n=3), in addition to a perception survey administered to students (n=111). The findings indicate a pronounced disjunction between policy and practice. Despite the institutional strategy emphasizing English as a tool for enhancing employability, operational deficiencies are evident, including an absence of proficiency-based student categorization and an excessive focus on passive, assessment-centered learning. The survey findings further substantiate this observation: while students indicate a degree of skill enhancement, the domain of speaking is perceived as the weakest, which corresponds with classroom observations that predominantly feature monologic presentations rather than interactive dialogues. The study concludes that without a pedagogical transition toward fostering active communication, the strategic objective of cultivating globally competent graduates is risked. Limitations of this research include its reliance on a single-institution sample. Practical implications suggest the necessity for curricular reform that emphasizes authentic, interactive tasks and the establishment of internal proficiency standards. Future research endeavors should investigate the longitudinal effects of such reforms across various MVS environments.